STRATEGI PENGEMBANGAN POTENSI PARIWISATA BERBASIS KEARIFAN LOKAL PADA DINAS KEBUDAYAAN, PARIWISATA, PEMUDA DAN OLAH RAGA KABUPATEN PONOROGO - Yayuk Herdianawati (JI@P, 2020)
The results showed that 1) The aspect of attraction, the strategy of one village onedestination carried out by the Office of Culture, Tourism, Youth and Sports,Ponorogo Regency and the Actor of Attraction Management are good enough inpresenting the attractiveness of objects tourist in Ngebel Lake. this program cansupport the tourism potential of an area in accordance with the advantages of thearea. The attraction offered is considered to be able to attract the attention ofvisitors or tourists. 2) Accessible aspects, the strategy carried out by thegovernment, namely: improving the quality of public transportation from 2017 -2021, increasing the quantity of tourist buses in 2019 and 2021, developingtelecommunications infrastructure, namely developing optical fiber networks anddeveloping micro networks using lower cable networks sea during 2017 - 2021.These activities have shown that progress is quite good, it takes time to berealized to the maximum, we need to support what the government has done andwill do in the future in terms of easily achieved aspects. 3) Facility Aspects(Amenitties), the strategy carried out by the government in the aspect of Facilities,namely the Special Economic Zones (KEK) has been running well, although ittakes time to achieve its objectives in order to obtain optimal results.